The World trade organizations and the environment - Rao, P K (London Macmillan Press, 2000)
WTO and the environment explains the role and limitations of liberalized international trade via-a-vis the global environment and sustain development. The first part of the book deals with a critical review of the economic foundation of traditional trade
Keywords: World trade organization; Free trade; Sustainable development